The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/biology10111188
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-homologue 1 Mediates Hormonally Regulated Dominance Rank in a Social Bee

Abstract: Dominance hierarchies are ubiquitous in invertebrates and vertebrates, but little is known on how genes influence dominance rank. Our gaps in knowledge are specifically significant concerning female hierarchies, particularly in insects. To start filling these gaps, we studied the social bumble bee Bombus terrestris, in which social hierarchies among females are common and functionally significant. Dominance rank in this bee is influenced by multiple factors, including juvenile hormone (JH) that is a major gona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 153 publications
(212 reference statements)
0
3
0
Order By: Relevance
“…However, in contrast to the honey bee, bumble bee foragers do not have higher Kr-h1 levels relative to nurses. Instead, in bumble bees, Kr-h1 is associated with JH-mediated division of worker reproduction and dominance rank ( Shpigler et al, 2010 ; Pandey and Bloch, 2021 ). Bumble bees are primitively eusocial insects that there are no obvious morphological differences between the queen and the workers.…”
Section: Other Biological Functions Of Kr-h1 In In...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to the honey bee, bumble bee foragers do not have higher Kr-h1 levels relative to nurses. Instead, in bumble bees, Kr-h1 is associated with JH-mediated division of worker reproduction and dominance rank ( Shpigler et al, 2010 ; Pandey and Bloch, 2021 ). Bumble bees are primitively eusocial insects that there are no obvious morphological differences between the queen and the workers.…”
Section: Other Biological Functions Of Kr-h1 In In...mentioning
confidence: 99%
“…Kr-h1 levels are found to be higher in dominant workers with active ovaries relative to subordinated individuals with undeveloped ovaries in queenless groups ( Shpigler et al, 2010 ). Knockdown Kr-h1 expression in bumble bees by a perfluorocarbon nanoparticles-based RNA interference protocol showed that bees with reduced Kr-h1 transcript abundance exhibited significantly reduced ovarian activity, less dominance behavior, and had lower dominance rank ( Pandey and Bloch, 2021 ). Therefore, Kr-h1 is associated with JH-mediated regulation of social organization in both bees, from labor division in honey bees to reproduction division and dominance rank in bumble bees.…”
Section: Other Biological Functions Of Kr-h1 In In...mentioning
confidence: 99%
“…Social dominance is a ubiquitous phenomenon, which is among social creatures from insects to primates ( 1 , 2 ). Social rank affects the distribution of dominant resources among individuals, and individuals with high rank tend to select areas where dominant resources are densely distributed, thus obtaining more relative resources.…”
Section: Introductionmentioning
confidence: 99%